The Politics of White Racial Identity and Vote Choice in the 2018 Midterm Elections. (30th May 2020) - Knuckey, Jonathan; Kim, Myunghee
Abstract : Objectives: This article examines the role of white racial identity or white racial group consciousness in the vote choice of whites for the U.S. House of Representatives in the 2018 midterm elections. Methods: Data from the 2018 American National Election Study (ANES) Pilot Study are analyzed using a logistic regression model. Results: White racial consciousness was a significant predictor of U.S. House vote choice in 2018, even after controlling for other relevant explanatory variables such as racial resentment, party identification, and ideology. The effects were especially evident for two quintessential swing groups: independents and moderates. Conclusion: In the first national election of the Trump era, white racial group consciousness became a relevant electoral cleavage and determinant of white vote choice at the subpresidential level. Given the rhetoric and action of Trump as president, the Republican Party has morphed into a white identity political party, not dissimilar to populist right‐wing parties in Europe. While this might reap electoral benefits for the Republican Party in jurisdictions with smaller minority populations, it is likely to cost the party support where there is greater racial diversity. In the long term, the politics of white identity is likely to be an impediment to the Republican Party's ability to expand its electoral base.